A Scoping Review of Modifiable Risk Factors in Pediatric Onset Multiple Sclerosis: Building for the Future - Julie Pétrin; Maximillian D.J. Fiander; Prenitha Mercy Ignatius Arokia Doss; E. Ann Yeh (MDPI AG, 2018)
Knowledge of the effect of modifiable lifestyle factors in the pediatric multiple sclerosis (MS) population is limited. We therefore conducted a scoping review, following the framework provided by Arksey and O'Malley. Four databases were searched for pediatric MS and modifiable lifestyle factors using index terms and keywords, from inception to May 2018. All quantitative and qualitative primary articles were included and limited to English and full text. Of the 7202 articles identified and screened, 25 full-text articles were relevant to our objective and were included. These articles focused on diet obesity, physical activity, and sleep. In cross-sectional analyses, these lifestyle factors were associated with increased risk of pediatric onset MS (POMS), and increased disease activity. Diet, particularly vitamin D and vegetable intake, was associated with reduced relapse rate. Obesity was linked to increased risk of POMS, and physical activity was associated with reduced relapse rate and sleep/rest fatigue. Thus, available studies of lifestyle related outcomes in pediatric MS suggest specific lifestyle related factors, including obesity, higher vitamin D levels, and higher physical activity may associate with lower disease burden in POMS. Studies reviewed are limited by their observational designs. Future studies with longitudinal and experimental designs may further clarify the role of modifiable lifestyle factors in this population.